2016
DOI: 10.1159/000447644
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Dentistry: Animal Model for Regenerative Endodontology

Abstract: Background: Ectopic tissue has been observed frequently in human root canal specimens when cell homing studies were performed at the dorsum of rodents. In contrast, pulp-like tissue formed when immature teeth were implanted on top of the rat calvaria. It was surmised, yet not tested, that the implantation site might affect tissue ingrowth. Methods: Four root sections from human immature molars cleaned with 5% sodium hypochlorite (NaOCl) followed by 17% ethylenediaminetetraacetic acid (EDTA) were implanted per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Unlike previous studies, Ruangsawasdi et al . () investigated the effects of the implantation site in an animal model for pulp regeneration. Pulp‐like tissue formation in teeth placed at the calvaria of rats was compared to that obtained at the dorsal area.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous studies, Ruangsawasdi et al . () investigated the effects of the implantation site in an animal model for pulp regeneration. Pulp‐like tissue formation in teeth placed at the calvaria of rats was compared to that obtained at the dorsal area.…”
Section: Resultsmentioning
confidence: 99%
“…Animal models, and more specifically rodent models, have been used extensively and have contributed greatly to the development and establishment of a wide range of translational approaches aiming to regenerate bone tissue. In this regard, the calvarial model has found great application in basic and applied research (Gomes & Fernandes 2011, Alquhali et al 2015, Ruangsawasdi et al 2016. The modified animal model used in this study allowed for assaying the effects of repairing agents on bone cells by determining the expression of important mediators involved in bone metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…, Ruangsawasdi et al . ). The modified animal model used in this study allowed for assaying the effects of repairing agents on bone cells by determining the expression of important mediators involved in bone metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies confirming this information were performed on culture cells or subcutaneous implantation. Ruangsawasdi, et al 25 (2016) demonstrated that the site can affect pulp regeneration. Considering that there are no in loco studies evaluating the angiogenesis on mature root canals, this study aimed to analyse the effect of VEGF on the angiogenesis of mature root canals in rat molars.…”
Section: Introductionmentioning
confidence: 99%